Proceedings of the FISITA 2012 World Automotive Congress Volume 8: Vehicle Design and Testing (II). (Lecture Notes in Electrical Engineering,, 2013)
Proceedings of the FISITA 2012 World Automotive Congress are selected from nearly 2,000 papers submitted to the 34th FISITA World Automotive Congress, which is held by Society of Automotive Engineers of China (SAE-China ) and the International Federation of Automotive Engineering Societies (FISITA). This proceedings focus on solutions for sustainable mobility in all areas of passenger car, truck and bus transportation. Volume 8: Vehicle Design and Testing (II) focuses on: •Automotive Reliability Technology •Lightweight Design Technology •Design for Recycling •Dynamic Modeling •Simulation and Experimental Validation •Virtual Design, Testing and Validation •Testing of Components, Systems and Full Vehicle Above all researchers, professional engineers and graduates in fields of automotive engineering, mechanical engineering and electronic engineering will benefit from this book.   SAE-China is a national academic organization composed of enterprises and professionals who focus on research, design and education in the fields of automotive and related industries. FISITA is the umbrella organization for the national automotive societies in 37 countries around the world. It was founded in Paris in 1948 with the purpose of bringing engineers from around the world together in a spirit of cooperation to share ideas and advance the technological development of the automobile.